Design and Manufacture of Antimicrobial New Sport Shoes Using Nano-silver to Prevent Germs and Viruses - Farzad Nobakht; Ehsan Fakhri Mirzanag; Negar Ashrafi; Poya Fakhraipur (Biyumikānīk-i varzishī, 2022)
Objective Attention Exercise is done for various purposes among athletes and the general public. One of the main problems in sports venues, especially with the spread of the corona virus, which has led to a threat to the health of the athlete community, is the presence of dangerous and pathogenic microorganisms such as germs, viruses, bacteria, etc. Therefore, the aim of the present study is to design and manufacture new antimicrobial shoes using nano-silver in order to prevent the spread of germs and viruses in the community of athletes. Methods The present study is an applied research carried out for designing and manufacturing new antimicrobial shoes using nano-silver in order to prevent the spread of germs and viruses in the athlete community. Results The results showed that the resistance of nanosilver solution at concentrations of 75, 50, 25 ppm against E. coli continues with a decrease of 70, 90 and 97.88%, respectively. The results also indicated that in concentrations of 50 and 75 the reduction in S. aureus bacteria is 70% and 90%, respectively. Moreover, the research findings demonstrated that from 100 ppm onwards, the reduction of S. aureus bacteria appears up to 99.99%. Conclusion The use of nano-silver in the design and manufacture of sports shoes to prevent and control many microbes and viruses can be useful.